Evidence of the Intercalative Redox Polymerization of Ehylenedioxythiophene into V2O5 ; Achievement of Highly Conducting Poly(3,4-Ethylenedioxythiophene)/V2O5 Nanohybrids - A. V. Murugan; C. W. Kwon; S. J. Hwang; M. H. Delville; J. Portier; G. Campet (Active and Passive Electronic Components)
We have established a novel method of inserting poly(3,4-ethylenedioxythiophene) (PEDOT) between the layers of V2O5 using a soft process of intercalation. The reaction takes place with the in situ polymerization of EDOT within the framework of crystalline V2O5 with different nominal EDOT/V2O5 ratios. The hybrids PEDOT/V2O5 exhibit a high electrical conductivity